Ruch ludowy w powiecie sieradzkim w okresie „odwilży popaździernikowej” (1956–1958) - Olejnik, Leszek (Zeszyty Wiejskie, 2016)
In the aftermath of the de-Stalinization processes (“political thaw”) the domestic peasant movement became markedly revived. The United People's Party (ZSL) was joined by genuine people’s activists who had been previously removed from active politics and accused for being in opposition to the communists. The district of Sieradz was also affected by the revival of the peasant movement. The ZSL activity was undergoing changes. The district management of the party fell into the hands of the activists who had been previously engaged in the structures of the opposition party of PSL, Polish People’s Party. The function of the district chairman of ZSL was at long last entrusted to Jan Plewiński in 1956, a dedicated people’s activist, a member of the people’s resistance movement during the Nazi occupation, and the leader of people’s party members in Sieradz. In the wake of the “October of 1956”, the members of the people’s party in Sieradz made an attempt of strengthening ZSL’s position in social and political life and increasing their independence of the governing PZPR (Polish United Workers Party). To achieve this goal they used political campaigns to the Seym and National Councils, among others. However, their endeavors remained ineffective as the PZPR policy, implemented with the aid of security agencies, put paid to the hopes of more profound political changes.